The Adventure of Napoleon’s Spy Beauchamp During the Occupation of Egypt: His Capture and Imprisonment in Istanbul (1798-1801) - Seydi Vakkas Toprak (Yakın Dönem Türkiye Araştırmaları)
France, which had had good relations with the Ottoman Empire, occupied Egypt in 1798. Meanwhile, Napoleon’s contact with Paris was cut off when the French Navy was burned by the British Navy in Abukir. Not wanting to return the places he’d taken on behalf of France, Bonaparte preferred to secretly send one of his diplomats to Istanbul as a representative without leaving room to declare war. He secretly sent his own man Beauchamp as a diplomat to Istanbul by way of an Ottoman galleon that had been stranded in Alexandria. However, Beauchamp was captured by the British fleet in the Mediterranean Sea and sent to Istanbul as a prisoner of war. The Ottoman Empire kept this diplomat captive in RumelifeneriCastle until the end of the war. This study evaluates the events surrounding this mission of Beauchamp in light of the resources in the Ottoman Archives.